2014
DOI: 10.4028/www.scientific.net/amm.633-634.1082
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of a Highly Compacted Soil Beds

Abstract: The clay loams of semi-solid consistency was tested under static loads. The test results have proved that high values of soil density can change operating conditions of artificial foundations significantly, i.e. a so-called plate effect can be observed. Due to high hardness values highly compacted soil beds allow distributing foundation loads on the considerable part of the area and reducing its value on the edge of the weak layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Larger porosity corresponded to more fragmentable soil, this effect was significant, and this finding was in agreement with Guérif (1990) and Hallett et al (2010). Usmanov et al (2014) claimed that it is more difficult to break harder soil because the pressure it receives during a collision is more evenly distributed throughout the soil, which reduces the concentration of the force and weakens the impact of the collision. Hallett et al (2010) suggested that soil fragmentation depends on not only the amount of porosity but also the geometric characteristics of the cracks, which is consistent with brittle fracture mechanics.…”
Section: Range Analysis Of Soil Fragmentation Characteristicssupporting
confidence: 74%
See 1 more Smart Citation
“…Larger porosity corresponded to more fragmentable soil, this effect was significant, and this finding was in agreement with Guérif (1990) and Hallett et al (2010). Usmanov et al (2014) claimed that it is more difficult to break harder soil because the pressure it receives during a collision is more evenly distributed throughout the soil, which reduces the concentration of the force and weakens the impact of the collision. Hallett et al (2010) suggested that soil fragmentation depends on not only the amount of porosity but also the geometric characteristics of the cracks, which is consistent with brittle fracture mechanics.…”
Section: Range Analysis Of Soil Fragmentation Characteristicssupporting
confidence: 74%
“…The two indicators showed an inverse relationship that indicated that the greater the hardness of the soil was, the less the soil fragmentation. These conclusions were the same as those of Usmanov et al (2014). In very hard soils, the soil particles adhere more closely and are more compact and resistant to damage (Xiao et al, 2019).…”
Section: Range Analysis Of Soil Fragmentation Characteristicsmentioning
confidence: 54%
“…-the simplified scheme of coordination of the replacement of import construction materials for the project with domestic materials, in case of impossibility of such replacement it is necessary to provide the mechanism of reimbursement, connected with the growth of exchange rate [22];…”
Section: Discussionmentioning
confidence: 99%
“…In eventology mathematical models of the HCS systems are considered within the framework of the eventological theory of systems (eventological system analysis) [1]. Starting from our paper [13], it is proposed to understand the eventological system (event system) as a set of events that consists of a free set of events (system basis) and events that are operationally related to events from the basis (system shell) [17][18][19][20][21][22].…”
Section: Eventological System Of Housing and Communal Servicesmentioning
confidence: 99%